Ethics and context in second language testing rethinking validity in theory and practice - Salaberry, M. Rafael 1963-; Weideman, Albert 1948-; Hsu, Wei-Li (Routledge, Taylor & Francis Group, 2024)
"This innovative, timely text introduces the theory and research of critical approaches to language assessment, foregrounding ethical and socially contextualized concerns in language testing and language test validation in today's globalized world"--
Keywords: Language and languages / Ability testing; Language and languages / Study and teaching / Moral and ethical aspects; Language and languages / Study and teaching / Psychological aspects; Context effects (Psychology); Essays; Aufsatzsammlung